DESIGN AND DEVELOPMENT OF INTERLEAVED BOOST CONVERTER AS A POWER QUALITY IMPROVEMENT IN ONE PHASE ROTARY WITH INDUCTIVE AND RESISTIVE LOADS - Winarno Fadjar Bastari; John Geral Mesah (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2019)
The unidirectional voltage source is obtained through an uncontrolled 220 Volt single phase full wave rectifier circuit. Installation of large amount capacitors as a filter affect input waveform. Due to the harmonics distort sinusoidal input voltage from the PLN grid. The difference in voltage waveforms and input currents that occur can affect the value of the resulting factor. Based on this problem, a study was made on theimprovement of power factors using a series of Interleaved Boost Converter which functioned as a series of Power Factor Correction (PFC) and voltage regulators with a setting method using Fuzzy logic. This Interleaved Boost Converter circuit is made to work in the condition of the Discontinues Conduction Mode (DCM) so that any load that is supplied to the circuit will make the system resistive. So, it is expected that thevoltage and input current waveforms will produce a factor value close to the unity value. The results of this study are the Interleaved Boost Converter series that can be used as a Power Factor Correction circuit and also as a voltage regulator. It improves power factor from 0.9 to 0.93.